Comparative Analysis of Financial Performance of Bank and Non-Bank Financial Institutions: Case Study of PT Bank Central Asia Tbk and PT BFI Finance Indonesia Tbk - Ilma Wulansari Hasdiansa (Abadi Institute, 2026)
This study aims to analyze and compare the financial performance between bank and non-bank financial institutions in Indonesia using a case study of PT Bank Central Asia Tbk (BCA) and PT BFI Finance Indonesia Tbk. The research method used is quantitative descriptive with a financial statement analysis approach, including balance sheet analysis, profit and loss, and financial ratios for the 2022–2024 period. The results of the study show that BCA has a more stable and superior financial performance in terms of profitability, operational efficiency, and strong capital. Meanwhile, BFI Finance showed a fairly good performance but was more vulnerable to financing risks and profit fluctuations. This difference is due to the business structure, funding sources, and operational characteristics of each institution. This research contributes to understanding the dynamics of financial sector performance and becomes a reference for investors and academics in decision-making.